IMPLEMENTASI PEMBELAJARAN PADA PROGRAM STUDI INDEPENDEN COURSE PRODUCT MANAGEMENT DI PT LENTERA BANGSA BENDERANG - Raihanah Aisyah Oktaviani; Eni Setyowati (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
In today's digital era, learning to develop digital skills s essential for students to prepare for their future careers. One way to achieve this s through the Kampus Merdeka program, ncluding the ndependent Study program. This program s expected to be a means for students to prepare themselves for changes n society, culture, the world of work, and rapid technological advances. The purpose of this study s to evaluate the mplementation of learning n the Certified ndependent Study program n Product Management organized by PT Lentera Bangsa Benderang, so that participants can understand the career opportunities available n the digital era. This research uses descriptive qualitative method, where the results are n the form of written or oral data and observable behavior of nformants. The results of the study show that the mplementation of learning n the Certified ndependent Study program at PT Lentera Bangsa Benderang has gone well, as seen from the program framework that encourages motivation and self-learning ability, as well as significant learning achievements with the preparation of a final project that reflects student understanding from the nitial material to the end. Therefore, the project-based learning approach at PT Lentera Bangsa Benderang can be a good foundation and reference for those who want to explore more deeply n the field of Product Management and build a career n the field.